Removing vitamin and trace mineral premixes from finisher diets (154 to 247 lb) did not affect growth performance, carcass characteristics, or meat quality - I H Kim; J H Lee; J S Park; Donald H Kropf; S L Johnston; P Sorrell; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1996)
Average daily gain; ADFI; F/G; dressing percentage; tenth rib fat thickness and depth; and color, firmness, and marbling of the longissimus muscle were not influenced by omitting the vitamin and(or) trace mineral premixes from diets during finishing (154 to 247 lb). Thus, omitting vitamin and trace mineral premixes can decrease diet costs without decreasing performance or meat quality of high-lean pigs.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Finishing pigs; Vitamins; Minerals; Meat quality; Growth